The DAMPAK NEGATIF JEMBATAN MERAH PUTIH TERHADAP KOMUNITAS SUBALTERN PENDAYUNG PERAHU DI TELUK AMBON - revaldo salakory (LIPI Press, 2021)
This research is expected to produce a strategy for the subaltern Poka-Galala boat rower in order to obtain the right strategy in order to get out of poverty caused by the construction of the red and white bridge so that the subaltern's income decreases and even loses their livelihood which has been a source of income to support their families. In addition, the research is also expected to be seen by stakeholders in the Maluku province and the Ambon City government in order to get the right solution in restoring the livelihood system that exists in the subordinate class of Poka-Galala boat rowers who depend on this work for a living. For this reason, it is hoped that it can produce an appropriate strategy for the subalterns, but will these subalterns be able to if they are not assisted both financially and morally in the form of motivation to fight for their rights and how to voice their rights to the government because basically subalterns are marginalized community groups? who are not able to express what they want they need strong voices sitting in government, and what about the attention of the government it self, the policy they are asking for is a policy that is truly in favor of the subaltern, if allowed then the government should be able to reengineer This beautiful bay of Ambon is a tourist spot in sea waters so that it can restore subaltern income which is reduced or even completely lost due to the construction of the red and white bridge.